Research on spring frost damage in cherries - Hüsnü Demirsoy; Leyla Demirsoy; Gregory A. Lang (Horticultural Science, 2022)
A frost occurred in spring following high temperatures in Michigan in 2007. It caused important crop losses. In this study, the damage the frost had on the flower buds of some cherry cultivars on 'Gisela 5' at the Southwest Michigan Research and Extension Center (SWMREC) and different cherry scion/rootstock combinations at the Clarksville Horticultural Experiment Station (CHES) were determined. In cherries, the frost damage at SWMREC varied from 26.7% to 99.3% depending on the cherry cultivar while it varied from 41.9 to 99.3% at CHES depending on the cherry combinations. 'Rainier/Gisela 6' at CHES and 'NY119' at SWMREC were promising. The bud development stage during the freeze, the cultivar, the rootstock, the ages of the trees and the low temperature level were effective in the spring frost resistance.